(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Abstract: This article explores the significance of creativity in personal development within the field of visual arts. It analyzes how learners develop aesthetic taste, critical thinking abilities, and personal expressive styles through art, and how pedagogical approaches can support these processes.